Board Leadership, Chief Executive Officer Optimism and Firm Innovation - Tuwey, Joel; Ngeno, Vincent (SEISENSE Journal of Management, 2019)
Purpose - Following the resource dependence and optimism theory, the study explored whether Chief Executive Officer (CEO) optimism moderates the link between board leadership and firm innovation in the financial sector. Design/Methodology - 130 financial institutions in Kenya were surveyed using cross-sectional and explanatory designs. Hypothesis testing utilized both moderated hierarchical regression models and mod-graphs. Findings - The results revealed that the board member’s openness and independence positively influence firm innovation. The moderated hierarchical regression results and figures in the mod-graphs reveal that CEO optimism enhances the association between the board member’s openness, independence, and firm innovation. Practical Implications - The results suggested that for financial institutions to be innovative, board members should be open to each other in terms of the private ideas as well as being independent about decisions made to spur the growth of the firms. Additionally, such boards should appoint CEOs who are optimistic about being innovative.